Shear strength studies of Kuantan bauxite - Syahmi Syafiq, Salahuddin (2019)
Soil investigation is an important step in Civil Engineering, especially in construction of buildings. One of the soil investigations is determining the shear strength of the soil, where shear strength of soil is important in determining the condition of the soil. It is also important in determining the designing of the foundation structure for building. For this study, Unconsolidated Undrained (UU) Triaxial Test was conducted to measure the displacement and the strength of soil. This study also examines the suitability of the soil as foundation for development purposed. From the test, soil deviator stress, number of stress applied and soil type are considered. From the results obtained from testing that were carried out, parameter of the shear strength, cohesion (“c”) and friction angle (“υ”) can be determined from Mohr Circle. From the parameter obtained, the value of the bearing capacity can be calculated and used for foundation construction.